Chromoblastomycosis with 18 years of evolution - Belda, Walter; Carvalho, Caroline H. C.; Passero , Luiz F. D. (International Journal of Research in Medical Sciences, 2023)
Chronic infectious, granulomatous and suppurative dermatosis, classified among the subcutaneous mycoses, caused by species of pigmented dematiaceous fungi, more prevalent in tropical and subtropical regions and caused by the traumatic implantation of dematiaceous fungal species, where the presence of muriform bodies are an expression of the causal agent in the grafted tissue, characteristic of chromoblastomycosis considered the second implantation mycosis in the world, it manifests itself with slow and progressive growth lesions of exophytic and verrucous plaques and black dots on the surface. The disease is considered a neglected and occupational disease, which occurs mainly among agricultural workers, and coconut and babassu harvesters, lumberjacks and traders of agricultural products. It is important to highlight that people at risk of contracting chromoblastomycosis work in tropical countries, where the temperature can be above 40 °C in summer, and generally refuse to wear protective equipment during the day (shoes, gloves, and clothes), although they know that this type of prophylactic measure can prevent different types of diseases. These vulnerable people often live in low-income countries and sometimes live far from medical services and, once infected, do not seek medical attention. We report below an exuberant and unusual case of lower limb chromoblastomycosis with a history of 18 years of evolution. The diagnosis was established by direct mycological examination, culture and microculture that identified the agent of the Fonsecaea species, and histopathological examination.